Mrs. Tsenhor : A Female Entrepreneur in Ancient Egypt - Donker van Heel, K. (American University in Cairo Press, 2014)
"From the papers she left behind, a picture emerges of a woman who had firm control over her own life. We are dealing here with an Egyptian woman in the fifth century BCE who owned houses and land, worked in the necropolis as a professional choachyte, and most probably did more business of which we are uinaware. In fact, what we have here is an unprecedented and privileged peek into the life of an ancient Egyptian girl next door that will never make it into the official history books"--Publisher description.